A bioluminescent imaging mouse model for Marburg virus based on a pseudovirus system - Li Zhang; Qianqian Li; Qiang Liu; Weijin Huang; Jianhui Nie; Youchun Wang (Human Vaccines & Immunotherapeutics, 2017)
Marburg virus (MARV) can cause lethal hemorrhagic fever in humans. Handling of MARV is restricted to high-containment biosafety level 4 (BSL-4) facilities, which greatly impedes research into this virus. In this study, a high titer of MARV pseudovirus was generated through optimization of the HIV backbone vectors, the ratio of backbone vector to MARV glycoprotein expression vector, and the transfection reagents. An in vitro neutralization assay and an in vivo bioluminescent imaging mouse model for MARV were developed based on the pseudovirus. Protective serum against MARV was successfully induced in guinea pigs, which showed high neutralization activity in vitro and could also protect Balb/c mice from MARV pseudovirus infection in vivo. This system could be a convenient tool to enable the evaluation of vaccines and therapeutic drugs against MARV in non-BSL-4 laboratories.